Wilms Tumors in Adults - Shah, Atta Ullah; Bilal, Hazrat; Nisa, Zeb un (Journal of Postgraduate Medical Institute, 2011)
Wilms tumors is a congenital disease found exclusively in children under the age of 4 years. Here a case of Wilms tumors in an adult women is described who presented with features of hypemephroma.